IKLIM KOMUNIKASI ORGANISASI DALAM MENUMBUHKAN MOTIVASI KERJA DAN KESEJAHTERAAN GURU DI PESANTREN MODERN DAAR AL ULUUM KISARAN KABUPATEN ASAHAN - Rial Sukma Hasibuan (QAULAN : Jurnal Komunikasi dan Penyiaran Islam, 2020)
This study aims to explain: First, organizational communication climate in growing motivation to work. Second, organizational communication climate in fostering the welfare of teachers. Third, the climate communication in motivation and well-being of teachers in Pesantren Modern Daar Al Uluum range in Asahan. The research data was obtained from interviews as 53orang include the foundation's president, headmaster, the deputy headmaster, kaur curriculum, teachers, and employees and jga field observations. Data analysis is qualitative descriptive. The results showed: Firstly, climate organizational communication and motivation has been carried out regularly and continuously, communication between the foundation with the school / madrasah principal and teachers carried out directly in the form of face to face, and indirectly in the form of a phone, sms or mail and almost all the teachers stated teaching is part of worship. Second, organizational communication climate and the welfare of teachers can be seen from the appreciation of the leadership is maximal, although not shaped material. Third, the climate communication in motivation and well-being of teachers is very important for communication, more effective could lead to employee motivation, motive welfare teacher at Pesantren Modern Daar Al Uluum range Asahan district based on the values ??of economic (materialistic) is not the main thing. Religious motif used is a testament to use the values ??of spiritual (religious) in each activity.